Flotation and adsorption of mixed cationic/anionic collectors on muscovite mica - Xu, Longhua; Wu, Houqin; Dong, Faqin; Wang, Li; Wang, Zhen; Xiao, Junhui (Minerals engineering, 2013)
► NaOL increases the adsorption of DAA attributed to its coadsorption. ► The incorporation of NaOL, DAA decreases the electrostatic head–head repulsion. ► MD simulations show that the coadsorption is attributable to synergies. ► The conclusions drawn from MD simulations coincide with experiments results. The adsorption of dodecylamine acetate (DAA), sodium oleate (NaOL) and DAA–NaOL mixtures on muscovite mica were investigated through flotation tests, zeta potential measurements, and pyrene fluorescence tests. The results show that the muscovite mica has a negative charge over the pH range 2–12. The muscovite mica did not float in the presence of NaOL alone. However, the recovery of muscovite mica ranged from ca. 80% (at pH 2) to 50% (at pH 11) using DDA alone. In the presence of mixed DAA–NaOL, recovery ranged from ca. 80% (at pH 2) to 90% (at pH 11). The individual cationic collectors DAA can be adsorbed strongly onto the muscovite mica, but no significant adsorption of anionic collectors NaOL can be detected by zeta potential measurements. In the mixed systems, the adsorption of both the cationic and anionic collectors are enhanced due to co-adsorption. The presence of NaOL in the mixture decreases the electrostatic head–head repulsion between the surface and ammonium ions and increases the lateral tail–tail hydrophobic bonds. Molecular dynamics (MD) simulations were conducted to further investigate the adsorption of DDA, NaOL, and DAA–NaOL on the (001) basal planes of muscovite using Materials Studio 5.0 program. The conclusions drawn from theoretical computations are in good agreement with experimental results.